Association of serum uric acid with increased risk of cancer among hypertensive Chinese. Issue 1 (24th April 2017) - Yang, Juan; Wang, Yupeng; Zhao, Qianqian; Zhang, Xianglin; Wang, Xiaobin; Qin, Xianhui; Zhang, Rong; Shen, Lin; Jiang, Xiaodong; Jiang, Hua; Lei, Yu; Wang, Binyan; et al.
Abstract : Several large prospective studies show an association between serum uric acid (SUA) and cancer, however there is a lack of evidence in China. We aimed to investigate the effects of SUA levels on cancer incidence and mortality in China. This study included 20, 577 adult hypertensive patients with valid SUA measurements who participated in the China Stroke Primary Prevention Trial where subjects were randomly assigned to receive a double‐blind treatment of either 10 mg enalapril (n = 10, 286) or 10.8 mg enalapril‐folic acid (n = 10, 291). Subjects were prospectively followed for a median of 4.5 years. Cox proportional hazards models were used to calculate hazards ratios (HR) of cancer risk associated with SUA. A total of 232 participants developed cancer. SUA was independently associated with increased cancer risk in the enalapril group [HR: 1.12, (95% CI: 1.03–1.22)]. Compared to the lowest tertile, combined subjects with SUA levels from the upper two tertiles had a higher risk of cancer in the enalapril group [T2 + T3: HR: 1.58, (95% CI: 1.02–2.47)]. In cancer site‐specific analyses, a positive association of SUA levels with digestive cancer and all fatal cancer was also observed [HR: 1.18, (95% CI: 1.09–1.27); HR: 1.15, (95% CI: 1.03–1.28), respectively] in the enalapril group. Interestingly, SUA levels were not associated with the risk of cancer or related mortality in the enalapril folic acid group. Our results suggest that elevated SUA is independently and positively associated with the risk of total cancer incidence, digestive cancer incidence and cancer mortality among hypertensive Chinese. Abstract : What's new? Serum uric acid (SUA), the end product of purine metabolism, is elevated in various diseases, among them hypertension and cancer. Previous studies, however, have proposed conflicting roles for SUA in cancer, with elevated SUA either protecting against or contributing to cancer risk. In the present evaluation of SUA and cancer in a cohort of Chinese adults with hypertension, elevated SUA was found to be positively associated with overall cancer risk, risk of digestive organ cancers and cancer mortality. The association was specific for enalapril‐treated patients. By contrast, cancer risk was attenuated among patients taking enalapril with folic acid supplementation.